A phage display study of interacting peptide binding partners of malarial S-Adenosylmethionine decarboxylase/Ornithine decarboxylase - Louw, Abraham Izak (University of Pretoria, 2013)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2008.